Relational Culture: Parental Support and Intimate Friendship in Strengthening Students’ Career Decision-Making Self-Efficacy - Kusnia Nikmatul Khasanah; Nurul Wahdah; Surawan Surawan (Bisma The Journal of Counseling, 2025)
Final-year students often experience confusion in making career choices because they lack strong self-efficacy in choosing a career. Therefore, this study aims to analyze the effect of parental support and intimate friendship on students' career decision-making self-efficacy (CDMSE) and to identify the forms of contribution. This research employed a mixed-methods approach with a sequential explanatory design. This research subjects were 202 students of Islamic Education Study Program (PAI), selected through a simple random sampling technique. Quantitative data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SmartPLS 4. Meanwhile, qualitative data were obtained from in-depth interviews with six students and analyzed through data reduction, data presentation, and conclusion drawing techniques. The results showed that parental support and intimate friendship had a significant effect on students' CDMSE, contributing 59%. These findings indicate that the social environment, particularly the role of parents and intimate friendship serves as an important conceptual factor in shaping career decision making self-efficacy. The implications highlight the need for synergy among families, peers, and educational institutions to optimally develop students' career readiness.